2021
DOI: 10.1192/bjo.2020.159
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study of perinatal hair cortisol concentrations in mother–infant dyads with severe psychiatric disorders versus healthy controls

Abstract: Background Maternal psychopathology during pregnancy is associated with negative outcomes in offspring. Increased placental transfer of maternal cortisol may contribute to mediate this association. Hair cortisol concentrations (HCCs) appear to be a good biomarker of long-term prenatal stress exposure. Little is known about the associations between severe maternal psychopathology and perinatal infant HCCs. Aims We assessed HCCs in the perinatal period in mother–infant dyads with and witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 68 publications
2
14
1
Order By: Relevance
“…With regards to a history of a depressive disorder, we found a trend towards higher cortisol values; this was not supported by the sensitivity analyses. In a previous study of our group we found a positive relationship between maternal general symptom severity and infant hair cortisol shortly after birth ([ 27 ]), but psychopathology in that sample was more heterogenic and severe than in the current study and we were not able to correct for childhood trauma. A recent study on the effect of maternal perinatal depression and anxiety on infant HCC at 12 months of age did not find a direct effect of maternal symptomatology either [ 26 ].…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…With regards to a history of a depressive disorder, we found a trend towards higher cortisol values; this was not supported by the sensitivity analyses. In a previous study of our group we found a positive relationship between maternal general symptom severity and infant hair cortisol shortly after birth ([ 27 ]), but psychopathology in that sample was more heterogenic and severe than in the current study and we were not able to correct for childhood trauma. A recent study on the effect of maternal perinatal depression and anxiety on infant HCC at 12 months of age did not find a direct effect of maternal symptomatology either [ 26 ].…”
Section: Discussioncontrasting
confidence: 84%
“…A recent larger study, not included in the review, found no association between a diagnosis of depression or anxiety and maternal HCC across pregnancy, nor with maternal and infant HCC at 12 months [ 26 ]. A previous study of our group in a small heterogenic sample of mothers with severe mental illnesses did find a positive association between maternal psychiatric symptom severity during pregnancy and infant HCC at 6 weeks ([ 27 ]). In this study maternal HCC also showed a strong association with infant HCC, but only in healthy women.…”
Section: Introductionmentioning
confidence: 89%
“…No correlation was found between maternal and infant HCC, paternal and infant HCC and maternal and paternal HCC within both groups, in contrast to earlier studies [48,49]. However, our results are in line with a more recent study, in which mother-infant dyads subjected to severe psychiatric disorders also showed no correlation between maternal and infant HCC [50].…”
Section: Discussionsupporting
confidence: 72%
“…Yet, there are controversial observations about hair cortisol in infancy and early childhood [ 9 ], reflecting the ongoing modulation of the HPA axis function and, therefore, findings vary among the different cultures, methodological tools and age groups that each study uses [ 10 ]. It is important to note that only few recent studies have examined the deviation of such correlation in a PMD group [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…A main limitation of the present study is the small sample size due to the child age limits and poor maternal response to participate in both sample groups. However, given the fact that mothers with perinatal mental disorders are a ‘hard-to-reach’ population, meaning that they constitute a sub-group of the population that is difficult to reach or involve in research, we believe that these preliminary findings, which only allow for an initial exploration and cannot be generalized in the population, do contribute to the scientific field as per previous studies [ 31 ]. The difficulty in interpreting the above results is increased considering the heterogeneity of maternal PMDs, as well as the severity of their symptoms and how they affect the child’s development and behavior.…”
Section: Limitationsmentioning
confidence: 90%